The intersection of Social Cohesion, Women Resilience and social Justice in Rural Communities in Developing Nations - Mbagwu, Felicia; Okafor, Samuel; Osilike, Chioma; Obiozo, Elizaeth; Ochiagha, Chibuike; Ugwoke, Ngozi; Ogbonnaya, Kingsley; Igwe, Ngozi; Okengwu, Mary (Acciones e Investigaciones Sociales, 2025)
Harmful traditional practices in sub-Saharan Africa are still problems with national and global social justice implications. While it has quickly become neglected tropical issues at the global level, it is still a deep challenge to the indigenous population especially in the rural communities. The present study focused on understanding the interaction of social cohesion and traditional harmful practices among women in rural communities in Nigeria. The study involved 1098 married women from community-based organizations. Survey design was applied in the study, while questionnaire instrument developed from social cohesion scale (Peterson & Hughey, 2004) and Work-Related Quality of Life (WRQoL) Scale (Edwards and Easton, 2007) was used in collecting data from the respondents. The collected data were analysed using inferential statistics. According to the findings of the study, there is a negative correlation between social cohesion and vulnerability to Harmful traditional cultural practices (rho-.407, P< .01), vulnerability to Harmful traditional practices is predicted by socioeconomic variables (R2= 0.850 P< .000), while identification with social cohesion is predicted by socioeconomic variables (R2= 0.932 P< .000)
Keywords: social cohesion; traditional harmful cultural practices; gender-based violence; social justice; sustainable development; community development